Waste Minimization Culture in Community-Based Enterprises - Wirandana, Raka (Omnia Tempus, 2024)
This study explores the cultural dimensions of waste minimization within community-based enterprises (CBEs), emphasizing their role as agents of grassroots sustainability. As environmental degradation escalates globally, CBEs—small, locally grounded organizations with social and environmental missions—have become pivotal in promoting sustainable practices through localized waste reduction behaviors. Despite the increasing relevance of CBEs in sustainability discourses, a gap remains in understanding how cultural values, leadership, education, and institutional reinforcement shape waste minimization practices. To address this, the study adopts a qualitative literature-based methodology, synthesizing findings from academic journals, policy reports, and empirical case studies published between 2010 and 2024. Using an inductive thematic approach, four key dimensions emerged: the influence of collective environmental values and community identity, the role of leadership and institutional reinforcement, the effectiveness of participatory education in behavioral change, and the integration of CBEs into long-term sustainability frameworks. The findings reveal that waste minimization culture in CBEs is driven by locally embedded norms and collective agency, reinforced by trust-based governance and peer influence. Furthermore, educational engagement and alignment with global agendas such as the Sustainable Development Goals (SDGs) enhance the scalability and durability of these practices. The study concludes that waste minimization should not be viewed solely as a technical or managerial function, but as a deeply cultural process rooted in community identity and social structure. These insights have both theoretical and managerial implications for scaling sustainability efforts in low-resource settings.